JUDGE AS A PUBLIC SERVANT - Zherobkina, Yevheniia; Maletov, Dmytro; Sevruk, Volodymyr; Pavlenko, Serhii; Serbyn, Nataliia (Revista Gênero e Interdisciplinaridade, 2020)
The topicality of this article is due to the intensification of the development and improvement of public administration in the world and the strengthening of the role of public service as a key characteristic of a democratic, rule of law state. The purpose of the article is to conduct a scientific study on the development of the model “judge-public servant” in Ukraine and the world. The leading research methods are general scientific and specific research methods, including methods of logic, analysis, comparison and more. The results of this study are the identification of the basic problems of functioning of the public service in Ukraine and the problems of determining the legal status of a judge as a public servant, as well as outlining the ways of overcoming problems. The significance of the results obtained is that the study may serve as a basis for outlining future changes to current legislation on the development of public service in Ukraine and the legal status of judges.